Methods of Assessing the Consumer’s Effectiveness of the enterprise’s Activities – the Assessment of Efficiency in the Context of Innovative Enterprises - Abramczyk, Damian (Journal of Finance and Financial Law, 2020)
The consumer strives to own more and more by spending income obtained from various sources. This one wants more than less. Enterprises, wanting to meet the client's expectations, produce goods which determine the quality of the company's future financial results. When purchasing goods from a manufacturer, the customer expects the highest possible quality products, assuming an average price level, adjusted to his preferences and financial possibilities. There may be times when the customer is not satisfied with the service or product. This event has an adverse effect on the company. In order to optimize this phenomenon, it is necessary to take preventive measures, which are almost always preceded by thorough research and analysis. The following article will present the methods of obtaining information on the degree of customer satisfaction with the goods purchased by the author, selected by the author. Social and psychological arguments that affect the final level of customer satisfaction will be presented. The consequences for the enterprise, related to the results of the customer satisfaction survey, will also be indicated.